Predictors of passing probability in the licensure examination for selected programs in the University of Southeastern Philippines - Callena, Eleonor T. (Southeastern Philippines Journal of Research and Development, 2019)
Performance of higher education institutions in licensure examinations is reflective of the effectiveness of their curricular programs. This study employed a causal design to evaluate graduates' academic attributes that can potentially determine the likelihood of passing the state-administered board examinations. Considered predictors variables are ratings in University admission test, average high school and college general point averages as well as course grades in major and professional courses. The test of significance of these variables was derived from a binary logistic regression. Results of the evaluation indicated that performance indicators varied across programs. The implications on students' academic attributes, the institution's admission and retention policy, assessment practices and quality assurance mechanism are discussed.